IPHONE USERS' PERCEPTION OF BRAND IMAGE, INNOVATION, AND PRODUCT QUALITY IN BUILDING LOYALTY AMONG MALIKUSSALEH UNIVERSITY STUDENTS - Rauzi Ramazalena; Depita Kardiati (CV. RADJA PUBLIKA, 2025)
Smartphones have evolved beyond communication tools to become symbols of personal expression and social status, with the iPhone being a prime example. This study aims to explore how iPhone users perceive brand image, innovation, and product quality, and how these elements shape their loyalty toward the brand. Data were collected through in-depth semi-structured interviews and analyzed using thematic analysis. The findings reveal that the iPhone's brand image is perceived as a symbol of prestige and self-identity, innovation is seen as a key differentiating factor, and product quality is highly rated in terms of durability and security. These three aspects synergistically reinforce user loyalty to the iPhone brand. The results emphasize the importance of consumer experience-based marketing strategies and provide practical implications for companies to maintain a strong brand image, relevant innovation, and high product quality to sustain customer loyalty, particularly among young users who act as digital trendsetters.